Pengaruh Material Handling Dan Tata Letak Terhadap Efektivitas Produksi Pada Perusahaan Manufaktur Otomotif Di Kawasan Jababeka I Cikarang - Novi Lestari; Aulia Affifah Ridwani (Jurnal Ekonomi dan Bisnis, 2021)
This study aims to analyze the effect of Material Handling and Layout on Production Effectiveness in manufacturing companies in the Jababeka Cikarang Industrial Estate. This type of research uses explanatory research, a research method that intends to explain the position of the variables studied and their influence between one variable and another. The sampling method in this study uses a saturated sampling technique. Data collection in this study was carried out by distributing questionnaires to 100 respondents to manufacturing companies in the Jababeka Cikarang Industrial Estate. The data obtained in this study were analyzed using multiple regression analysis. The results of this study indicate that the effect of Material Handling and Layout on Production Effectiveness. The data is then tested for data quality by using the validity test, reliability test, after testing the quality of the data then tested using the classical assumption test and multiple regression. The classical assumption test used consists of normality test, multicoinearity test, and heteroscedasticity test. Then the data were analyzed using the coefficient of determination test, t test, and f test. The results of this study indicate that the effect of Material Handling and Layout has a positive effect on Production Effectiveness